Estudo das catelicidinas no plasma seminal de garanhões e das interleucinas na resposta inflamatória pós-iseminação artificial em éguas - Fioratti, Eduardo Gorzoni [UNESP] (2013)
In the equine species, uterine interleukin expression and seminal plasma cathelicidins can modulate the magnitude and persistence of the post-breeding inflammatory reaction. The objectives were to verify the presence of cathelicidins in the stallion seminal plasma and characterize the uterine immune response by pro and anti-inflammatory interleukins. Seminal plasma was obtained by semen collection of 15 stallions and submitted to SDS-PAGE and DOT-blotting tests. Three experiments were designed to study interleukin expression during baseline (T1), after seminal plasma infusion (T2) and artificial insemination (T3). Endometrial cytology and cell collection as well as ultrassonographic evaluations were performed to access interleukin mRNA through qPCR during three randomly assigned consecutive estrous cycles, 24 (M1), 48 (M2) and 72 hours (M3) after an ovulation was induced. Endometrial mRNA expression in mares resistant and susceptible to persistent post-breeding endometritis was identified for the following pro-inflammatory cytokines: IL-1β, IL-6, IL-8, IL-10 e TNF-α. Total seminal plasma protein concentrations ranged from 6.3 to 25.6 mg/mL. SDS-PAGE analysis identified the existence of three proteic bands with molecular weight similar to what was previously reported for equine cathelicidins. Evaluated stallions showed values < 339.6 ng for eCATH1, < 141.3 ng for eCATH2 and < 283.4 for eCATH3. At M2, resistant and susceptible mares could not be separated through cytology or ultrassonography, even though the presence of sperm strongly stimulates uterine inflammatory reaction. At M3, susceptible mares showed higher uterine fluid accumulation and lower uterine clearance. Pró-inflammatory mRNA expression was higher in susceptible mares and interleukin-10 mRNA expression was similar between resistant and susceptible mares